Identification and complete cDNA sequence of the missing Drosophila MCMs: DmMCM3, DmMCM6 and DmMCM7. - Feger, G. (Gene, 1999)
The minichromosome maintenance (MCM) gene family consists of six members (MCM2, 3, 4, 5, 6 and 7) in Saccharomyces cerevisiae as well as in humans. Each family member plays an essential role in the replication of DNA. In Drosophila melanogaster only three members, DmMCM2, DmMCM4/dpa and DmMCM5/DmCDC46, have been studied. In addition, two other partial sequences were recently reported. Using degenerate primers and low stringency PCR conditions six different DNA sequences were identified with highest sequence similarity to MCM2, 3, 4, 5, 6 and 7. Sequence analysis of full length cDNA clones corresponding to the MCM3, 6 and 7 fragment proves the existence of six MCM genes in Drosophila melanogaster. Strong homology to the human counterparts, mRNA expression analysis and physico-chemical properties suggest a conserved function in DNA replication for DmMCM3, 6 and 7.